2015
DOI: 10.1161/strokeaha.114.007584
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Thrombosis in the Absence of Headache

Abstract: Background and Purpose-Although headache is the most common symptom in cerebral venous thrombosis, 5% to 30% of patients do not report headache at baseline. Characteristics of these patients have not been investigated. ; P=0.009) were more common among patients without headache. Outcome at last follow-up was worse in patients without headache (modified Rankin Scale, 0-1; 76% versus 89%; P=0.04; mortality, 13% versus 5%; P=0.05), but after adjustment for prognostic variables, headache was not an independent pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 10 publications
0
34
0
2
Order By: Relevance
“…The association of motor deficit with ASS is also confirmed by other studies, but in contrast to the Mahale study, aphasia was a predictor of ASS, in ISCVT, and in the VENOPORT study ASS were associated with sensory deficits . Conversely, the risk of early seizures in patients presenting with isolated intracranial hypertension is low (<3%) and the comparison of patients with and without headache as a presenting symptom has shown that seizures are significantly more common in patients without headache (58% vs. 32%) . It can be obviously concluded that involvement of brain parenchyma at or near the motor cortex leading to motor or sensory deficit predisposes patients to ASS.…”
Section: Discussionmentioning
confidence: 99%
“…The association of motor deficit with ASS is also confirmed by other studies, but in contrast to the Mahale study, aphasia was a predictor of ASS, in ISCVT, and in the VENOPORT study ASS were associated with sensory deficits . Conversely, the risk of early seizures in patients presenting with isolated intracranial hypertension is low (<3%) and the comparison of patients with and without headache as a presenting symptom has shown that seizures are significantly more common in patients without headache (58% vs. 32%) . It can be obviously concluded that involvement of brain parenchyma at or near the motor cortex leading to motor or sensory deficit predisposes patients to ASS.…”
Section: Discussionmentioning
confidence: 99%
“…Plausible presentations, therefore may range from absent clinical signs and symptoms, to vague or severe signs and symptoms related to acute increases in intracranial pressure (1,2). Headache is the most common presenting symptom by far accounting for approximately 90% of patients diagnosed with DVST, followed by seizures (6,48,49). …”
Section: Discussionmentioning
confidence: 99%
“…Headache is the most common symptom in CVT, but patients without headache are sometimes reported. In ISCVT, CVT patients without headache were frequently older male patients [9,10,13]. Our study showed a low incidence of headache, 62.5%, which we suspected was due to the high percentage of older men in our study.…”
Section: Discussionmentioning
confidence: 49%
“…A meta-analysis of 17 clinical studies showed that oral contraceptive use, Leiden mutation of Factor V, and hyperHcy were recognized as statistically significant risk factors 8). A multinational (21 countries), multicenter (89 centers) prospective observational study entitled the International Study on Cerebral Vein and Dural Sinus Thrombosis (ISCVT) [9][10][11][12][13] examined 624 cases of CVT and reported that the prevalence of hyper-Hcy is 4.5%. However, Boncoraglio et al reported from Italy that 10 of 26 patients (38.5%) with CVT had hyper-Hcy7).…”
Section: Archivos De Medicina Issn 1698-9465 Journal Of Neurology Andmentioning
confidence: 99%